(untitled) (Journal of actual problems of jurisprudence, 2018)
In this article, the concept of “legal convergence” is considered as a relatively new and relevant category of the general theory of state and law, representing in general terms the process of convergence of national legal systems, legal families, legal constructions and constructions in conditions of legal globalization. Based on the latest scientific research, interpretations, and also through the prism of the social science theory of convergence of the second half of the twentieth century, the question of modern understanding of this concept is covered. The conclusion is drawn about complex, contradictory and not fully studied structure, the mechanism of influence on the legal field and the consequences of legal convergence. The idea of XXI century as global convergences in all social spheres can be accounted for by axioms. The most important trends in the globalization process are the emergence of meaningful development and development of people, nations and civilizations, the process of globalization and integration. The process of rusting, combing with others, is reflected in the coordination of social ideological and paradigmatic platforms based on universal humanistic values. It is characterized by changes in the direction and regulation of social life, in the first place – the right (as universal as a civilized formulation of public relations). Key words: globalization, legal globalization, convergence theory, legal convergence.